Modified Vaccinia Virus Ankara as a Viral Vector for Vaccine Candidates against Chikungunya Virus - Juan García-Arriaza; Mariano Esteban; Daniel López (Biomedicines, 2021)
There is a need to develop a highly effective vaccine against the emerging chikungunya virus (CHIKV), a mosquito-borne Alphavirus that causes severe disease in humans consisting of acute febrile illness, followed by chronic debilitating polyarthralgia and polyarthritis. In this review, we provide a brief history of the development of the first poxvirus vaccines that led to smallpox eradication and its implications for further vaccine development. As an example, we summarize the development of vaccine candidates based on the modified vaccinia virus Ankara (MVA) vector expressing different CHIKV structural proteins, paying special attention to MVA-CHIKV expressing all of the CHIKV structural proteins: C, E3, E2, 6K and E1. We review the characterization of innate and adaptive immune responses induced in mice and nonhuman primates by the MVA-CHIKV vaccine candidate and examine its efficacy in animal models, with promising preclinical findings needed prior to the approval of human clinical trials.